Integration of heterogeneous medical and biological data with electronic personal health records - Savoska, Snezana; Ristevski, Blagoj; Blazheska-Tabakovska, Natasha; Jolevski, Ilija; Bocevska, Andrijana; Trajkovik, Vladimir (Medical Informatics, Biometry and Epidemiology (MIBE), 2023)
The shortage of data for patients with chronic and other diseases and previous medical treatments shows significant weakness in the diagnoSnezana Savoska1 Blagoj Ristevski1 sis and treatment of patients. Due to the healthcare system insufficiency, Natasha Blazheska-Tabakovska1 patients with comorbidities might not survive the diseases, especially when the disease is novel. The lack of information on patients’ genetic disorders, especially when they are unaware of them, also contributes Ilija Jolevski1 to increased patient deaths. This conveys the necessity to integrate Andrijana Bocevska1 medical and health data with various biological omics and other data, Vladimir Trajkovik2 especially in pandemic circumstances. Patients’ health data matters are apparent, but they are stored in multiple hospitals and health systems such as electronic health records (EHRs), healthcare institutions, 1 Faculty of Information and Communication and laboratories. Furthermore, biological data are often not integrated and cannot be used by patients, physicians, and specialists to treat Technologies, University “St. particular diseases. Although the urgent need for healthcare and med- Kliment Ohridski” – Bitola, ical data integration is apparent, personal data protection regulations Republic of Macedonia are severe. They do not allow much progress in the area without imple- 2 Faculty of Computer Science menting security and privacy standards for patient healthcare data. and Engineering, “Ss. Cyril One solution for this issue is setting a personal health record (PHR) as and Methodius” University of an integrative system for the patient. Many ontological frameworks have Skopje, Republic of been proposed to unify the record formats, but none of them is accepted Macedonia as a healthcare standard. The efforts toward approving the Health Level Seven (HL7) standards and the common medical coding systems ensure further data integration. Some efforts are made to associate particular diseases with data obtained from external environmental sensors that measure disease-associated data. Using these data, which are called exposome, the increasing symptoms of particular diseases influenced by external factors can be clarified. This paper suggests a cloud-based model for integrating healthcare and medical data from different sources such as EHRs, health information systems, and measurement sensors into the PHR as the first stage toward integrating patient health data. Besides the patients’ personal and clinical data, various omics data should be integrated for improved individualized disease prognosis and treatment of the patients. These data are stored in the cloud following the required data security and privacy standards.
Keywords: electronic health records, personal health records, Internet of Medical Things, data integration, omics data, healthcare information system